Geological-Geochemical and Mineralogical Properties of Basalt Rocks of Karakalpakstan - Yuldashev Sh.Sh. Toshpulatov D.; Djaksimuratov Karamatdin Mustapaevich; O’telbayev Azizbek Alisher o’g’li; O’razmatov Jonibek Ikromboy o’g’li (Researchparks Publishing, 2021)
Basalt properties, Basalt identified locations, areas of application of basalt, Basalts are new fire-resistant and heat-resistant materials; metal substitutes; electrical insulators of various potentials; acid-resistant products; composite materials; Portland cement and others that can be used in various fields.